بناء برنامج ارشادي مستند الى نظرية ستامفل لتنمية المواجهة الاستباقية لدى طالبات المرحلة الإعدادية (Journal of the College of Basic Education, 2024)
The current research aims to identify building a counseling program based on Stampfel's theory to develop proactive confrontation among middle school students. The purpose of achieving the goal of the research, the researchers carried out the following procedures. Building a proactive confrontation scale consisting of (33) items distributed over three domains. The first domain includes (planning), the second domain includes (defining goals), and the third domain includes (advance preparation for confrontation). After extracting the psychometric characteristics of the scale, a counseling program was built according to the Boders and Dardi model, which included (12), suggested counseling sessions to develop proactive confrontation among middle school students. Relying on the techniques and methods of Stampfel's theory and extracting the virtual validity of the program after presenting it to a group of arbitrators specialized in psychological counseling and educational guidance. It was applied to an exploratory sample consisting of (24) female students who appeared to have low scores in the proactive confrontation compared to the hypothetical mean of (93). The two researchers used appropriate statistical methods to achieve the goal of the research.